Maslahah Analysis on Early Marriage of Broken Home Women: Case Study In Gubuk Sukun, West Tanak Beak Village - muttaqien, Imamal; Wadi, Lalu Tambeh (STAINI Press, 2026)
Marriage is a sacred bond between a man and a woman with the purpose of forming a family that is sakinah, mawaddah, and rahmah, as explained in Surah Ar-Rum verse 21. However, the phenomenon of early marriage remains prevalent, especially among girls from broken homes who are driven by various factors such as family instability, economic hardship, and social pressure. This study examines early marriage among girls from broken homes in Dusun Gubuk Sukun, Tanak Beak Barat, using a case study approach and the analysis of maslahah mursalah. Data were collected through interviews and documentation involving those who had early marriages and their families. The findings indicate that although underage marriage is not legally recognized by the state, from the perspective of maslahah mursalah, such marriages may bring benefits to girls from broken homes. This research highlights the importance of a contextual approach in understanding the practice of early marriage, as well as the need for synergy between religious values, state law, and the social realities of the community.